Management Accounting System, Perceived Environmental Uncertainty and Corporate Performance in the Nigeria Breweries Sector. - Etim, Etim Osim (Archives of Business Research, 2019)
The study examined the effect of Perceived Environmental Uncertainty on the Implementation of Management Accounting Systems on performance of Breweries Companies in Nigeria. Survey design method was adopted to gather data from respondents using structured questionnaire designed using likert-scale. Data were analysed using correlational and inferential statistics. Results shows R2 of 0.759 and F-value of 172.88 which provide ample confirmation on the effect of adoption of Management Accounting Systems (MAS) based on Perceived Environmental Uncertainty (PEU) on organizational performance in the Breweries sector of the Nigeria economy following the high correlational positive relationship between the variable studied. It is concluded that adoption of Management Accounting systems based on perceived Environmental Uncertainties has enhanced the performance of the sector when tailored to the level of Environmental Uncertainties facing the Sector: It is recommended that contingent approach should be adopted in designing MAS so as to ensure provision of reliable and relevant information for product cost and pricing.